Effects of Vasoactive Drug Use on Hemodynamics in Critical Disease Pediatic Patients - Melike Ersoy; Metin Karaböcüoğlu (Galenos Yayinevi, 2019)
Introduction:The fact that critically ill pediatric patients have hemodynamic and metabolic characteristics different from that in adults plays a key role in the selection of vasoactive agent. The aim of this study was to compare the effects of vasoactive agent and agent groups on hemodynamics in order to effectively regulate impaired hemodynamics in critically ill pediatric patients, to provide early diagnosis, time-sensitive and targeted treatment and reduce side effects. Methods:Disease severity, vital signs, renal function, and laboratory data of 103 patients aged 1 to 18 years, who were treated in the pediatric intensive care unit and administered one or more vasoactive agents, were evaluated.Results:The average Pediatric Risk of Mortality (PRISM III-24) score in the dobutamine group was significantly higher than in the adrenalin-dobutamine group (p=0.048), and no statistically significant difference was observed between the other groups (p>0.05). There was a statistically significant difference in the mean cardıac apex beat between dopamine, dobutamine, dopamine-dobutamine and dopamine-adrenaline groups (p=0.0001, p=0.0001 p=0.007 and p=0.011, reespectively). A statistically significant difference was observed in systolic blood pressure (SAB) between dopamine-dobutamine, dopamine-adrenaline and dopamine-dobutamine-adrenaline groups (p=0.003, p=0.00 and p=0.005, respectively). The S0 lactate levels in the adrenaline group were found to be statistically significantly higher than those in dopamine and adrenaline-dobutamine and dopamine-dobutamine-adrenaline groups (p=0.048, p=0.036 and p=0.045. There was a significant difference in S4 lactate values between dopamine-adrenaline and adrenaline-dobutamine groups and between dobutamine and adrenaline groups (p=0.045 and p=0.047, respectively). There was no statistically significant difference in the average central venous oxygen saturation (ScVO2) between dopamine, dobutamine, dopamine-dobutamine, dopamine-adrenaline, adrenaline-dobutamine, dopamine-dobutamine-adrenaline, dopamine-dobutamine-adrenaline-noradrenaline and adrenaline groups (p>0.05). A statistically significant difference was observed between the mean amounts of urine S0, S24 and S48 in the dobutamine group (p=0.002). The average S0 urine volume in the dobutamine group was found to be statistically significantly lower than the average S24, S48 urine volume (p=0.01 and p=0.03, respectively). No statistically significant difference was observed between the other times and groups (p>0.05).Conclusion:Blood lactate levels were significantly higher in the adrenaline group than in the other groups, while no significant difference was found in cardiac apex beat, SAB, ScVO2 and amount of urine between the groups. This elevation was limited to the first 4 hours, and the use of adrenaline together with dopamine and/or dobutamine significantly reduced the incidence of hyperlactatemia compared to the use of adrenaline alone. The use of dobutamine alone significantly increased the amount of urine within hours.